Progressing beyond SLMTA: Are internal audits and corrective action the key drivers of quality improvement? - Robert N. Maina; Doris M. Mengo; Abdikher D. Mohamud; Susan M. Ochieng; Sammy K. Milgo; Connie J. Sexton; Sikhulile Moyo; Elizabeth T. Luman (AOSIS, 2014)
Background: Kenya has implemented the Strengthening Laboratory Management Toward Accreditation (SLMTA) programme to facilitate quality improvement in medical laboratories and to support national accreditation goals. Continuous quality improvement after SLMTA completion is needed to ensure sustainability and continue progress toward accreditation. Methods: Audits were conducted by qualified, independent auditors to assess the performance of five enrolled laboratories using the Stepwise Laboratory Quality Improvement Process Towards Accreditation (SLIPTA) checklist. End-of-programme (exit) and one year post-programme (surveillance) audits were compared for overall score, star level (from zero to five, based on scores) and scores for each of the 12 Quality System Essential (QSE) areas that make up the SLIPTA checklist. Results: All laboratories improved from exit to surveillance audit (median improvement 38 percentage points, range 5-45 percentage points). Two laboratories improved from zero to one star, two improved from zero to three stars and one laboratory improved from three to four stars. The lowest median QSE scores at exit were: internal audit; corrective action; and occurrence management and process improvement (< 20%). Each of the 12 QSEs improved substantially at surveillance audit, with the greatest improvement in client management and customer service, internal audit and information management (≥ 50 percentage points). The two laboratories with the greatest overall improvement focused heavily on the internal audit and corrective action QSEs. Conclusion: Whilst all laboratories improved from exit to surveillance audit, those that focused on the internal audit and corrective action QSEs improved substantially more than those that did not; internal audits and corrective actions may have acted as catalysts, leading to improvements in other QSEs. Systematic identification of core areas and best practices to address them is a critical step toward strengthening public medical laboratories.